Households and the Emergence of Cities in Ancient Mesopotamia. Issue 2 (2nd July 2014) - Ur, Jason
Abstract : The world's first cities emerged on the plains of Mesopotamia (modern Iraq and Syria) in the fourth millennium bc. Attempts to understand this settlement process have assumed revolutionary social change, the disappearance of kinship as a structuring principle, and the appearance of a rational bureaucracy. Most assume cities and state-level social organization were deliberate functional adaptations to meet the goals of elite members of society, or society as a whole. This study proposes an alternative model. By reviewing indigenous terminology from later historical periods, it proposes that urbanism evolved in the context of a metaphorical extension of the household that represented a creative transformation of a familiar structure. The first cities were unintended consequences of this transformation, which may seem 'revolutionary' to archaeologists but did not to their inhabitants. This alternative model calls into question the applicability of terms like 'urbanism' and 'the state' for early Mesopotamian society.